PENGARUH PROMO PENGEMBALIAN DANA, DISKON, DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN MENGGUNAKAN DOMPET DIGITAL DENGAN KEPERCAYAAN MEREK SEBAGAI VARIABEL INTERVENING (Studi pada Dompet Digital GoPay di Indonesia) - Nydia Widya Soraya; Suryono Budi Santosa (Diponegoro Journal of Management, 2023)
ABSTRACT Technological developments have a big impact because with the presence of new technology that continuously makes transactions easier. New innovations have sprung up in the banking world such as the existence of electronic payment instruments such as digital wallets. Increased public interest in using e-wallets for transactions can encourage the growth of various non-cash payment products. In Indonesia there are many digital wallet (e-wallet) applications, some of which are GoPay, OVO, LinkAja, DANA, etc. One of them is GoPay as a digital wallet that can grow rapidly. From 2017 to 2020 GoPay was drastically able to occupy the first position (market leader) for digital wallet service providers, but throughout its journey GoPay took second place in the most popular digital wallet survey according to the Kadance Survey (2021) where the first position was occupied by OVO. This phenomenon is certainly an interesting study of why GoPay's ewallet service was able to beat its competitors, which originally occupied the first position to become the second position as a digital wallet service. In the world of marketing, promotion is one way to retain and increase consumers. Based on previous research, variables such as cashback, discounts, and service quality are indeed factors that can create purchasing decisions because brand trust has been created as a marketing strategy that can increase purchasing decisions using digital wallets. The number of samples used was 140 respondents and selected by purposive sampling and data collection methods through questionnaires. The analytical tool used in this study is the AMOS 24 program. The results of this study indicate that cashback, discounts, and service quality have a positive and significant effect on brand trust. Furthermore, brand trust also has a positive and significant effect on purchasing decisions